Circular RNA circ_0057558 Controls Prostate Cancer Cell Proliferation Through Regulating miR-206/USP33/c-Myc Axis - Ding, Tao; Zhu, Yanjun; Jin, Huimin; Zhang, Ping; Guo, Jianming; Zheng, Jianghua (Frontiers in Cell and Developmental Biology, 2021)
We previously reported the elevated expression of circ_0057558 in prostate cancer tissues and cell lines. Here, we aimed to determine the biological function of circ_0057558 in prostate cancer. In the current study, circ_0057558 knockdown in prostate cancer cells significantly suppressed cell proliferation and colony formation, but induced cell arrest and enhanced the sensitivity to docetaxel. Bioinformatics analysis prediction and RNA-pull down assay identified miR-206 as the potential binding miRNA of circ_0057558. miR-206 expression was negatively correlated with circ_0057558 expression in prostate cancer tissues. miR-206 mimics rescued the function of circ_0057558 overexpression on prostate cancer cells. Further, the bioinformatics analysis and Luciferase assay identified Ubiquitin Specific Peptidase 33 (USP33) as a target gene of miR-206. USP33 mRNA expression was inversely correlated with miR-206 expression and positively correlated with circ_0057558 expression in prostate cancer tissues. USP33 overexpression partially blocked the effects of miR-206 mimics on prostate cell proliferation. USP33 could bind and deubiquitinate c-Myc. Increased c-Myc protein by circ_0057558 overexpression was partially reversed by miR-206 mimics. MYCi361, a specific inhibitor for c-Myc, was more effective in anti-proliferative activity against prostate cells with higher level of circ_0057558 in primary prostate cancer cells and patient-derived xenograft (PDX) model. Collectively, circ_0057558 gives an impetus to cell proliferation and cell cycle progression in prostate cancer cell lines by sponging miR-206 and positively regulating the transcription of the miR-206 target gene USP33.